Remote Sensing: Gis - Mason,PJ (2004)
Geological phenomena vary in space and time and this basic trait makes geology a particularly suitable application field for Geographical Information Systems (GIS). A GIS is a computer-based tool for the mapping and analysis of things that exist on, and events that happen on Earth. It is, therefore, a sophisticated but general-purpose tool and one which can be applied in many ways to many problems, and especially so in geosciences. There have been a number of technological advances, including the development of GIS, which have transformed the work of the geoscientist over the last 15–20 years. Until the 1980s, GIS was used and developed mainly by the geographical community and generally in government organizations and research institutions. The wider geological community has been, until relatively recently, a little sceptical about its operational success in solving complex geological problems. The first GIS systems were pretty cumbersome hardware and software suites, with high-end functionality that required programming skills to operate. These have evolved into highly functional desktop systems, which anyone can learn to use, and which are part of a growing, multibillion dollar, worldwide industry. GIS functionality developed very quickly, with the advanced statistical and 3D analytical modules, which had been considered requirements only of the advanced GIS community, becoming the selling points for desktop GIS. Multivariate and geo-statistical methods laid the foundations of the geological application of GIS. Specialized exploration software, in the late 1970s and 1980s, had many features present in current GIS suites, such as those of Zycor....